Misconception Analysis Of Misconception Of Grade VI Science Material On Photosynthesis Theme - Indri Rahmawati, Indri Rahmawati; Atmojo, Idam Ragil Widianto (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to identify and analyze misconceptions among sixth-grade students at SD Negeri 58 Mojo, Sragen Regency, regarding the concept of photosynthesis using a four-tier test instrument. The research design employed is descriptive quantitative with a sample of 20 students. The instrument consisted of 10 four-tier items based on key indicators of the photosynthesis topic. Data were collected through direct testing and quantitatively analyzed based on the percentage of misconceptions. The results revealed that the highest misconception occurred in identifying the plant part responsible for photosynthesis (80%). Most misconceptions stem from poor conceptual understanding of leaf structure and chloroplast function. These findings confirm that the four-tier test is effective in diagnosing student misconceptions and can be utilized as a diagnostic tool in science education. It is recommended that teachers use visual-based and hands-on approaches when teaching photosynthesis to minimize misconceptions. Further research could explore the effectiveness of misconception-based learning interventions with a broader population